γδ T Cells in Antimalarial Immunity: New Insights Into Their Diverse Functions in Protection and Tolerance - Dantzler, Kathleen W.; Jagannathan, Prasanna (Frontiers in Immunology, 2018)
Uniquely expressing diverse innate-like and adaptive-like functions, γδ T cells exist as specialized subsets, but are also able to adapt in response to environmental cues. These cells have long been known to rapidly proliferate following primary malaria infection in humans and mice, but exciting new work is shedding light into their diverse functions in protection and following repeated malaria infection. In this review, we examine the current knowledge of functional specialization of γδ T cells in malaria, and the mechanisms dictating recognition of malaria parasites and resulting proliferation. We discuss γδ T cell plasticity, including changing interactions with other immune cells during recurrent infection and potential for immunological memory in response to repeated stimulation. Building on recent insights from human and murine experimental studies and vaccine trials, we propose areas for future research, as well as applications for therapeutic development.